141k views
4 votes
Solve the given system by substitution.

Solve the given system by substitution.-example-1
User Zavg
by
4.4k points

2 Answers

0 votes

-4(2) + 3 = -5
8 - 1 = 7
User Tasnuva Leeya
by
4.7k points
1 vote

Answer:

(-2/3, -23/3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

-4p + q = -5

p - q = 7

Step 2: Rewrite Systems

p - q = 7

  1. Add q on both sides: p = q + 7

Step 3: Redefine Systems

-4p + q = -5

p = q + 7

Step 4: Solve for q

Substitution

  1. Substitute in p: -4(q + 7) + q = -5
  2. Distribute -4: -4q - 28 + q = -5
  3. Combine like terms: -3q - 28 = -5
  4. Isolate q term: -3q = 23
  5. Isolate q: q = -23/3

Step 5: Solve for p

  1. Define equation: p - q = 7
  2. Substitute in q: p - (-23/3) = 7
  3. Simplify: p + 23/3 = 7
  4. Isolate p: p = -2/3
User Mrkschan
by
4.9k points